Pengaruh Penggunaan Vermikulit Terhadap Pertumbuhan Planlet In Vitro Kelapa Genjah Kopyor - NURHAINI MASHUD; ENGELBERT MANAROINSONG (Buletin Palma, 2010)
The Effect of Vermiculate in Y 3 Media Substituted by Coconut Water toGrowth of Kopyor Dwarf Coconut PlantletsThe research was conducted at Tissue Culture Laboratory of Indonesian Coconut and Palms Research Institute, Manado, North Sulawesi, from August to December 2009. The aim of of this research was to determine the effect of vermiculate to development of rooting system of dwarf kopyor coconut in vitro plantlets. The result showed that application of vermiculate on liquid Y 3 media which substituted by coconut water improved the rooting system of the plantlets. Number of lateral roots/planlet on liquid Y 3 media which substituted by 25 ml coconut water/l media higher (98,67) than those in media substituted by 50 ml coconut water/l media. These plantlets were vigor, so that it is expected that they could survive in the screen house during acclimatitation.